The Golden Mill - Barrera Cárdenas, Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The Bourdeur Family was a traditional family that lived in Tolouse, France in the 1870’s. Two brothers were descendants of this family. Reyner, was born in 1871, and his brother Victorine, was born in 1872. These children were raised during the boom of the industrial revolution, but each followed a different life path. Reyner was attracted to cartography, and Victorine decided to become a literature teacher.